Network analytical model of tandem queuing RED and ERED - CHI Xue-fen; ZHAO Ying-ying (Tongxin xuebao)
Based on the tandem queuing network theory,tandem queuing RED and ERED analytical models were established which emprise multiple network nodes.The RED algorithm with exponent packet loss distribution function was derived（ERED）.In probability generation function domain,departure process of a node was derived and then fitted for the follow-up node’s arriving process,thus,the multiple nodes relayed congestion control sinarios could be depicted.Network performances of three tandem queuing AQM algorithms（RED,ERED and DT） were presented by solving queu-ing system.The problems of AQM parameter setting and its effect on system performance were analyzed.Considering two types of traffic with different degrees of burst,performance indicators for each node in tandem queuing system are investigated,and specially,system end-to-end performance indicators are derived.